Kerangka Integratif Etika Bisnis Syariah dalam Penilaian Kelayakan Usaha dan Mitigasi Risiko Kegagalan - Tahara Maharani (STAI Sulthan Syarif Hasyim, 2026)
Islamic business ethics place Islamic values such as trustworthiness (amanah), honesty, justice, and the prohibition of riba as the moral foundation in conducting business activities. This study is motivated by the high rate of business failures, particularly among micro, small, and medium enterprises (MSMEs), which are often caused by weak governance and low ethical integrity among entrepreneurs. The purpose of this research is to examine the role of Islamic business ethics in assessing business feasibility and to formulate failure mitigation strategies consistent with Sharia principles. This study employs a qualitative method with a library research approach, referring to primary sources such as the Qur’an, Hadith, and DSN-MUI fatwas, as well as secondary literature from national and international academic journals published between 2017 and 2025. Data were analyzed descriptively and analytically using content analysis to identify the relationship between Sharia ethical principles, business feasibility indicators, and risk mitigation strategies. The results show that Islamic business ethics serve as both a moral guideline and a practical mechanism for realizing fair, transparent, and accountable Islamic governance. The principles of tauhid, amanah, ihsan, and justice strengthen public trust, encourage profit-and-loss-sharing financing, and reduce the risk of business failure. The implications of this study emphasize that the implementation of Islamic business ethics not only enhances profitability but also ensures blessings (barakah) and business sustainability, thereby serving as a conceptual foundation for entrepreneurs, financial institutions, and regulators in building a resilient, competitive, and socially beneficial halal business ecosystem.